The circ_0032822 Promotes the Proliferation of Head and Neck Squamous Cell Carcinoma Cells Through miR-141/EF3 Signaling Axis - Zhang, Shuajia; Han, Jiahui; Fu, Jing (Frontiers in Oncology, 2021)
Head and neck squamous cell carcinoma (HNSCC) refer to an epithelial malignant tumor that originates in the head and neck, and over 600,000 new cases are reported every year, However, the overall prognosis is still poor due to local recurrence and distant metastasis after surgery. The circ_0032822 has been reported upregulated in human oral squamous cell carcinoma; However, the detailed function or mechanism remain unknown. In this study, we confirmed the upregulation of circ_0032822 in HNSCC tumor tissues. Functionally, the overexpression of circ_0032822 significantly promoted the proliferation of HNSCC cell lines along with the S phase arrest and reduced apoptosis, while downregulation of circ_0032822 has the opposite effect in vitro. Mechanistic analysis showed that circ_0032822 acted as a competing endogenous RNA of miR-141 to diminish the repressive effect of miR-141 on its target E2F3. In conclusion, we demonstrated that circ_0032822 functions as a tumor oncogene in HNSCC and that its function is regulated via the miR-141/E2F3 axis.